Preconceito e discriminação para além das salas de aula: sociabilidades e cultura juvenil no ambiente escolar - COELHO, Wilma de Nazaré Baía (Universidade Federal do Pará, 2018)
This article analyzes the engendered and lived youth sociabilities in the school environment. Through them, we question the way in which youth culture is related to the school and also how they deal with prejudice and discrimination. We argue that the school is an important space for sociability in youth culture. It is where significant part of social relations takes place. Nevertheless, this important dimension of the formation process is not an object of pedagogical intervention. The perceived sociabilities incorporate a meaningful discriminatory constituent based on color, race, gender and religious affiliation prejudice. Practiced in classrooms, hallways, courtyards and school courts, they are not object of educational action but in borderline cases, subject to punishment.